Mitogen-Activated Protein Kinase Signaling Mediates Morphine Induced-Delayed Hyperalgesia - de Freitas, Bárbara Guimaraes; Pereira, Leandro Márcio; Santa-Cecília, Flávia Vianna; Hösch, Natália Gabriele; Picolo, Gisele; Cury, Yara; Zambelli, Vanessa O. (Frontiers in Neuroscience, 2019)
The use of morphine, the standard opioid drug, is limited by its undesirable effects, such as tolerance, physical dependence, and hyperalgesia (increased pain sensitivity). Clinical and preclinical studies have reported development of hyperalgesia after prolonged opioid administration or after a single dose of intrathecal (i.t.) morphine in uninjured rats. However, whether a single standard systemic morphine dose is sufficient to decrease the nociceptive threshold in rats is unknown. Here, we showed that a single morphine subcutaneous injection induces analgesia followed by a long-lasting delayed hyperalgesia in uninjured and PGE2 sensitized rats. The i.t injection of extracellular signal-regulated kinase (ERK) inhibitor blocked morphine-induced analgesia, without interfering with the morphine-induced hyperalgesia. However, i.t. injection of SB20358, a p38 inhibitor and SP660125, a JNK inhibitor, decreased the morphine-induced hyperalgesia. Consistently with the behavioral data, Western Blot analysis showed that ERK is more phosphorylated 1h after morphine, i.e., when the analgesia is detected. Moreover, phospho-p38 and phospho-JNK levels are upregulated 96h after morphine injection, time that coincides with the hyperalgesic effect. Intrathecal (i.t.) oligodeoxynucleotide (ODN) antisense to cAMP-responsive element binding protein (CREB) attenuated morphine-induced hyperalgesia. Real-time polymerase chain reaction (RT-PCR) analysis showed that CREB downstream genes expressions were significantly up-regulated 96h after morphine injection in spinal cord. Together, our data suggest that central ERK is involved in the analgesic and hyperalgesic effects of morphine while JNK, p38 and CREB are involved in the morphine-induced delayed hyperalgesia.